Effect of Zhizhu Kuanzhong capsule on functional dyspepsia: Protocol for a systematic review and meta-analysis of randomized controlled trials. Issue 6 (February 2018) - Lin, Haixiong; Wang, Xiaotong; Du, Xiuting; Wang, Junyue; Li, Yusi; Zhang, Ren
Abstract: Background: Functional dyspepsia (FD) is a gastrointestinal disorder affecting people in the globe. Spleen-deficiency syndrome is one of its basic syndromes. Zhizhu Kuanzhong capsule was the most frequent Chinese herbal formula used in the spleen-deficiency researches. We aim to assess the effectiveness and safety of Zhizhu Kuanzhong capsule on FD. Methods: A systematic literature search for randomized controlled trials (RCTs) from their inception until December 31, 2017 will be conducted using 7 databases: PubMed, Cochrane Library, Embase, VIP Database, Chinese National Knowledge Infrastructure, Wanfang Data, and Chinese BioMedical Database. Inclusion the trials of Zhizhu Kuanzhong capsule which evaluate motilin level, clinical syndrome, and side effect in people with FD. The primary outcome measures will be motilin level, clinical syndrome integral, and clinical total effective rate. Data extraction and risk of bias assessments will be performed by 2 reviewers independently. Methodological and reporting quality of included studies will be assessed by the consolidated standards of reporting trials for Chinese herbal medicine formulas. All statistical analyses will be conducted using RevMan V.5.3 software. Funnel plots, Begg's test, and Egger's test will be developed to evaluate reporting bias. Results: This review will assess the effect of Zhizhu Kuanzhong capsule on clinical total effective rate, symptom remission rate, plasma motilin level, and safety of FD in patients. Conclusion: The conclusion of our study will provide updated evidence to judge whether Zhizhu Kuanzhong capsule is an effective intervention for patients with FD. Abstract : Supplemental Digital Content is available in the text